New generation of ecofriendly reagents based on organosolv lignin nanoparticles: Environmental assessment for an Au flotation circuit - Peppas A.; Politi C.; Pantazakou E.; Skenderas D. (Journal of Mining and Metallurgy. Section A: Mining)
Froth flotation is the leading process for the selective separation of minerals and the beneficiation of ores. The principle of the method depends on the different wettability properties of the minerals, specifically on the hydrophobicity of the surfaces, which is either inherent or imparted to the minerals through reagents. Despite their widespread and long-standing use, they are considered highly hazardous and toxic and their decomposition poses a potential risk in terms of safety, health, and environmental impact. A new viable alternative, that promotes sustainable development, is the production and utilization of organosolv lignin nanoparticles. This study examines the environmental benefits of producing of lignin nanoparticles from birch wood as and partially replacing xanthate collectors with lignin nanoparticles for the treatment of 1 tonne of mined ore, subjected to flotation. In order to quantify the environmental impact, a life cycle assessment (LCA) was conducted for an Au flotation circuit. The analysis demonstrated that the introduction of organosolv lignin into the flotation process along with the reduction of sodium isopropyl xanthate (SIPX) resulted in the decrease of the environmental footprint and in particular the reduction of climate change and fossil fuel depletion by 16.79% and 3.8%, respectively.